Dahili Aciller - Borazan, İsmail; Top, Ahmet Ali; Ferhatlar, Mehmet Esat; Şentürk, Mücahit; Danış, Faruk; Oymak, M.Server; Karcıoğlu, Özgür; Beşer, Zafer; Karabay, Onur; Kabakçı, Ahmet; Özensoy, Habibe Selmin; Kemancı, Aykut; et al. (2024)
-